2012
DOI: 10.3748/wjg.v18.i46.6829
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive treatment of pancreatic necrosis

Abstract: Each minimally invasive approach though was found to be safe and feasible in multiple reports. With these new techniques, treatment of infected pancreatic necrosis remains a challenge. We advocate a multidisciplinary approach to this complex problem with treatment individualized to each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 33 publications
0
55
0
6
Order By: Relevance
“…While this series does not reflect a randomised trial or even a direct comparison, the median number of procedures required per patient was 2 (range: 1-5), which is lower than most retroperitoneal necrosectomy series, where it varies from 3 to 5. 20 However, lower numbers have been reported from endoscopic, 21 transperitoneal 2 and combined approaches. 12,13 There was one death in our series of patients, which was due to respiratory complications that developed after the patient had been discharged to his local hospital and more than 90 days after the necrosectomy procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this series does not reflect a randomised trial or even a direct comparison, the median number of procedures required per patient was 2 (range: 1-5), which is lower than most retroperitoneal necrosectomy series, where it varies from 3 to 5. 20 However, lower numbers have been reported from endoscopic, 21 transperitoneal 2 and combined approaches. 12,13 There was one death in our series of patients, which was due to respiratory complications that developed after the patient had been discharged to his local hospital and more than 90 days after the necrosectomy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations outlined above (of a descriptive series versus a trial), this compares extremely favourably with other published mortality rates following retroperitoneoscopic necrosectomy of 0-26%. 14,20 A systematic review of endoscopic necrosectomy suggested outcomes may be improved with this route compared with open or direct retroperitoneal access as overall morbidity and mortality rates were found to be 27% and 5% respectively, which was lower than with surgical minimal access methods. 17 The multicentre PENGUIN (Pancreatitis, ENdoscopic transGastric versUs primary necrosectomy in patients with Infected Necrosis) trial by the Dutch Pancreatitis Study Group randomised patients to either endoscopic or surgical necrosectomy and found endoscopic necrosectomy to be superior with significantly less new onset organ failure (0% vs 50%, p=0.03) and fewer pancreatic fistulas (10% vs 70%, p=0.02).…”
Section: Discussionmentioning
confidence: 99%
“…[15] On the basis of a meta-analysis of 8 researches considering 286 patients the percutaneous drainage of infected pancreatic necrosis was efficient in 44% of them. [16] Percutaneous drainage can be exploited together with endoscopic drainage as a method of a multiple approach to the necrotic cavity, [9,14,17] particularly when it comes to penetration of necrosis down the abdominal cavity, up to the minor pelvis. [18] It was proved that the use of percutaneous drainage during endoscopic treatment of WOPN decreases the amount of endoscopic and radiological procedures as well as hospitalization time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are often skewed by the characteristics of the study, and so there is a need for an update to establish which of the currently available techniques should be used in specific cases of INP. Based on the study of various review articles [16][17][18][19], the approaches described can be classified in four broad groups: percutaneous, retroperitoneal, laparoscopic (transperitoneal) and endoscopic (endoluminal). In turn, each of these approaches can be considered as the definitive single treatment or can be used as the initial approach in combination with others [13].…”
Section: Introductionmentioning
confidence: 99%